UPAYA MENINGKATKAN HASIL BELAJAR KIMIA MELALUI MODEL NUMBERED HEADS TOGETHER DI SMAN 1 SUNGAI RAYA - Baihaki, Muhammad (At- Tarbawi, 2019)
Data obtained in this study include: student learning outcomes taken from giving daily test questions given at the end of the cycle, the ability of teachers in learning taken from the observation sheet, student activities in learning taken from the observation sheet, and data about student reflection on lessons learned from the questionnaire at the end of each meeting. Indicators of success in this study are: (1) if ? 70% of the total students are categorized as complete with the criteria of completion of learning if the value of the evaluation results in cycles I and II, ? 70, (2) if student activities in learning ? 70% are measured by look at the student observation sheet. The results of the study in the first cycle showed the average value of student learning outcomes of 65.29 and the percentage of mastery learning at 58.82%. Student activity 61.36%, percentage of teacher ability 68.33%. While the results of research in the second cycle the average value of student learning outcomes by 75.88 and the percentage of mastery learning by 88.24%. Student activity 84.09%, and the percentage of teacher ability by 85%. From this study it was concluded that using the NHT learning model could improve the learning outcomes of chemistry and class X.1 student activities in semester II of the 2014/2015 academic year on the subject matter of nomenclature of compounds and reaction equations.